Deciphering food hawkerpreneurship: Challenges and success factors in franchising street food businesses in Malaysia - Chong, Daniel Ka Leong *; Stephenson, M. L. * (SAGE, 2020)
This study investigates the challenges and identifies the critical success factors in transforming traditional hawker food into a franchisable business, principally within the context of Malaysia. This study aims to provide guidelines that could support the process of enterprising traditional street food businesses, especially to assist the mobilization and promotion of hawkerpreneurship for existing traditional food hawkers and future adopters. A total of five hawkerpreneurs and four traditional hawkers were qualitatively assessed through semi-structured interviews. As a result, four critical challenges that both hawkerpreneurs and traditional hawkers encountered were identified, namely: (1) exploring the unknown (2) high capital investment for total “make-over” (3) lack of knowledge in brand repositioning, and (4) resistance to automation and standardization, particularly as a way to retain authenticity. By considering these concerns, young entrepreneurs and financial investors can assess the potentiality and feasibility of hawker food, and identify areas to focus on in running a successful traditional street food business. The results of this study could further assist in developing the support mechanisms and start-up strategies that encourage the adoption of hawker food entrepreneurship among Malaysians.